2018
DOI: 10.1002/alr.22248
|View full text |Cite
|
Sign up to set email alerts
|

In‐office balloon sinus dilation versus medical therapy for recurrent acute rhinosinusitis: a randomized, placebo‐controlled study

Abstract: BackgroundA limited number of studies have demonstrated symptomatic improvement for recurrent acute rhinosinusitis (RARS) patients after endoscopic sinus surgery. In this randomized, controlled study we evaluated 24‐week outcomes for balloon sinus dilation (BSD) performed in‐office (IO) with medical management (MM) as compared with MM only for RARS patients.MethodsAdults diagnosed with RARS were randomized to groups with BSD plus MM (n = 29) or MM alone (n = 30). Patients who received MM alone also received a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 20 publications
0
14
0
Order By: Relevance
“…Current guidelines delineate a role for BSD in RARS, although CT imaging is required showing evidence of ostial occlusion and mucosal thickening 510 . The first randomized, placebo‐controlled, unblinded trial showed that patients who received in‐office BSD and medical management for RARS (n = 29), compared to patients receiving in‐office sham procedure and medical management (n = 30), reported significant improvements in CSS and RSDI scores at 8 and 24 weeks follow‐up 511 . BSD also significantly reduced mean number of sinus infections at 24 weeks follow‐up.…”
Section: Recurrent Acute Rhinosinusitis (Rars)mentioning
confidence: 99%
See 1 more Smart Citation
“…Current guidelines delineate a role for BSD in RARS, although CT imaging is required showing evidence of ostial occlusion and mucosal thickening 510 . The first randomized, placebo‐controlled, unblinded trial showed that patients who received in‐office BSD and medical management for RARS (n = 29), compared to patients receiving in‐office sham procedure and medical management (n = 30), reported significant improvements in CSS and RSDI scores at 8 and 24 weeks follow‐up 511 . BSD also significantly reduced mean number of sinus infections at 24 weeks follow‐up.…”
Section: Recurrent Acute Rhinosinusitis (Rars)mentioning
confidence: 99%
“…Nonetheless, the REMODEL study provides level 1 evidence that BCD may be a potential treatment option for patients with limited disease involving the maxillary and/or anterior ethmoid sinuses, where appropriate medical therapy has failed. A recent randomized, placebo‐controlled trial in patients with RARS showed BCD plus medical management proved superior to medical management alone further potentially supporting its role in minimal diseased states 511 …”
Section: Surgery For Chronic Rhinosinusitismentioning
confidence: 99%
“…If surgery for RARS is performed, maxillary sinus surgery and anterior ethmoidectomy are the most common procedures [308,317,318]. Balloon sinuplasty also shows positive effects on QoL and number of acute infections [319]. After sinus surgery, there is a significant reduction of the number of acute infections.…”
Section: Postoperative Outcomementioning
confidence: 99%
“…Compared to medical therapy, surgical treatment leads to a greater improvement of the disease-specific quality of life in the SNOT-22 [308]. Patients under medical treatment often change to a surgical approach in the further course (33-76 %) [308,319]. There is often a deterioration of QoL prior to this change [308].…”
Section: Specific Measures Of Health-related Quality Of Lifementioning
confidence: 99%
“…1,2 Prospective studies have shown that BCD is noninferior to endoscopic sinus surgery (ESS) for improving symptoms and quality of life in adult and pediatric patients with chronic rhinosinusitis (CRS). [3][4][5][6][7] However, issues with these findings have been raised regarding sample size and obvious discrepancies in disease severity. 8 Proper comparison of BCD and ESS has been challenging, as patients undergoing BCD usually have lower disease burden.…”
Section: Introductionmentioning
confidence: 99%